2020
DOI: 10.1186/s12912-020-0405-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of the nursing education reform on the educational environment in Tajikistan: a repeated cross-sectional analysis

Abstract: Background: A well-functioning education system for family nurses is a priority of the primary health care reform in Tajikistan. In 2015/2016, a baseline study was carried out to measure the educational environment at two nursing colleges, in Kulob and Dushanbe. Building on the study's recommendations, the educational reform has addressed several key issues to improve the educational environment among nursing students with a focus on strengthening competency-based learning and clinical skills. A follow-up stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Improvements in the educational environments of nurses in Tajikistan have also been documented. (22) Kazakhstan o cially joined the Bologna Declaration in March 2010. The main characteristics are: (1) the minimum entry quali cations involve completing 10 years of general education (15-16 years old); (2) introducing a three-cycle higher education system consisting of bachelor's, master's and doctoral studies; and (3) implementation of a system of quality assurance, to strengthen the quality and relevance of learning and teaching (23).…”
Section: Educationmentioning
confidence: 99%
“…Improvements in the educational environments of nurses in Tajikistan have also been documented. (22) Kazakhstan o cially joined the Bologna Declaration in March 2010. The main characteristics are: (1) the minimum entry quali cations involve completing 10 years of general education (15-16 years old); (2) introducing a three-cycle higher education system consisting of bachelor's, master's and doctoral studies; and (3) implementation of a system of quality assurance, to strengthen the quality and relevance of learning and teaching (23).…”
Section: Educationmentioning
confidence: 99%
“…In modern education, the essence of the concept of "educational environment" and its various aspects were studied by Aars and Christensen [9], Abed et al [10], Alahmadi [11], Al-Maroof et al [12], Andersson [13], Berrani et al [14], Bondarenko et al [15], Camacho et al [16], Chrysafiadi et al [17], Dotsenko [18], Fuentes-Moreno et al [19], Horbatiuk et al [20], Huh [21], Kerimbayev et al [22], Kyslova et al [23], Lechthaler et al [24], Lawless and Riel [25], Lee et al [26], Morze and Kucherovska [27], Mousavi et al [28], Orlando et al [29], Sahu et al [30], Shapovalov et al [31], Smogorzewska et al [32], Stratulat et al [33], Tleubay et al [34], Uchitel et al [35], Yang et al [36] and others. The educational environment is considered as a factor of education from the standpoint of understanding education as a special sphere of social life.…”
Section: Related Workmentioning
confidence: 99%
“…Nine negatively-worded items must be reverse scored for analysis and interpretation (Lechthaler et al, 2020 ) Previous research has indicated that various personal characteristics, such as teaching experience and gender, explain differences in teaching behavior and student outcomes (Inda-Caro et al, 2019 ). The different components of teaching and learning, understanding the current situation of medical nursing students, and the type of education being provided were taken into consideration.…”
Section: Introductionmentioning
confidence: 99%